MicroRNA-15b regulates reversion-inducing cysteine-rich protein with Kazal motifs (RECK) expression in human uterine leiomyoma - Guan, Yichun (Reprod Biol Endocrinol, 2016)
BACKGROUND: Human uterine leiomyoma (fibroids; LYO) are the most common benign neoplasms in reproductive-aged women. Dysregulated extracellular matrix and irregular LYO reversion-inducing cysteine-rich protein with Kazal motifs (RECK) expression are thought to be mediated by aberrant microRNA (miR) expression. The relationship of miR-15b and RECK expression in LYO has not been studied. METHODS: The expression levels of miR-15b and RECK were determined by quantitative RT-PCR, Western blot, and immunohistochemistry in cultures derived from commercial primary leiomyoma (cpLYO) and myometrial (cpMYO) cell lines and leiomyoma (pLYO) and myometrium (pMYO) tissue from surgical samples respectively. The relationship between miR-15b and RECK expression in cpLYO and pLYO (compared to their respective myometrial controls) was evaluated following transfection of cell cultures with either miR-15b mimic or inhibitor. RESULTS: Elevated levels of miR-15b were observed in cpLYO (2.82-fold; p = 0.04) and pLYO cell (1.30-fold; p = 0.0001) cultures respectively compared to corresponding MYO cell controls. Following transfection with miR-15b mimic, cpLYO cells (0.62-fold; p < 0.0001) and pLYO cells (0.68-fold; p < 0.0001) demonstrated reduced RECK protein expression. Following transfection with miR-15b inhibitor, cpLYO cells (1.20-fold; p < 0.0001) and pLYO cells (1.31-fold; p = 0.0007) demonstrated elevated RECK protein expression. RECK protein expression was reduced in pLYO tissues (0.73-fold; p < 0.0001) and pLYO (0.47-fold; p = 0.047) cells when compared to the corresponding MYO tissue controls. CONCLUSION: Our findings suggest that miR-15b negatively regulates RECK expression in LYO, and increased miR-15b and decreased RECK expression may contribute to the pathobiology of LYO. The functional significance of miR-15b and RECK expression warrants further investigation as potential therapeutic targets for the treatment of human LYO.